The role of nursing in the management of cerebrovascular diseases - Leonard-Pérez, Luisa María; Vega-Montalvo , Teresa; Pérez-Díaz , Yuleisis (Revista Científica Estudiantil de Ciencias Médicas de Matanzas, 2025)
Cerebrovascular diseases represent one of the leading causes of mortality and disability worldwide. Among them, stroke is the most common and devastating entity, with a significant impact on the quality of life of patients and their families. In this context, the role of nursing is fundamental, as nursing professionals are involved not only in direct patient care but also in prevention, education, and rehabilitation. This article analyzes the role of nursing in the management of CVD, highlighting its importance in prevention, acute care, and rehabilitation, as well as its impact on clinical outcomes.